The longest-lived metazoan, Arctica islandica, exhibits high mitochondrial H2O2 removal capacities - Munro, Daniel; Rodríguez, Enrique; Blier, Pierre U (Elsevier BV, 2022)
A greater capacity of endogenous matrix antioxidants has recently been hypothesized to characterize mitochondria of long-lived species, curbing bursts of reactive oxygen species (ROS) generated in this organelle. Evidence for this has been obtained from studies comparing the long-lived naked mole rat to laboratory mice. We tested this hypothesis by comparing the longest-lived metazoan, the marine bivalve Arctica islandica (MLSP=507 y), with shorter-lived and evolutionarily related species. We used a recently developed fluorescent technique to assess mantle and gill tissue mitochondria’s capacity to consume hydrogen peroxide (H2O2) in multiple physiological states ex vivo. Depending on the type of respiratory substrate provided, mitochondria of Arctica islandica could consume between 3-14 times more H2O2 than shorter-lived species. These findings support the contention that a greater capacity for the elimination of ROS characterizes long-lived species, a novel property of mitochondria thus far demonstrated in two key biogerontological models from distant evolutionary lineages.